The effect of direct and indirect competitive differentiation style in learning some offensive skills in handball - Azadeen, Moad K.; Yousef, Saadi O.; Ibrahim, Ibrahim M. (Humanities Journal of University of Zakho, 2017)
The research aims to figure out the effect of direct and indirect competitive differentiation style and showing explained show (classical) in learning some offensive skills in handball, and compare the results of both direct and indirect competitive differentiation and explained show (classical) styles in learning some offensive skills in handball. The researchers used thee experimental approach because the suitability to research. The community of research selected of second year students in school of Physical Education University of Duhok (2014-2015), they were 65 students divided to three groups. While the sample was consisted 42 students represented three groups, where each group consisted of 14 students, where chosen randomly after excluded some students because of homogeneity of research. After the homogeneity of research between the groups, two instructional programs were set up for the chosen skills, where the period of program was 6 weeks 2 times a week for 90 minutes. SPSS was used to analyze the data. The researchers conclude: The direct and indirect competitive differentiation styles (classical) have a positive effect on learning some offensive skills in handball. The second experimental group that used the direct competitive differentiation styles better improvement than the first experimental group that used the indirect competitive differentiation styles and the third experimental group that used the classical styles in learning some offensive skills in handball